Impact of free on‐site vaccine and/or healthcare workers training on hepatitis B vaccination acceptability in high‐risk subjects: a pre‐post cluster randomized study. (25th July 2014) - Launay, O.; Le Strat, Y.; Tosini, W.; Kara, L.; Quelet, S.; Lévy, S.; Danan, J.; Réveillon, J.; Houdayer, J.; Bouvet, E.; Lévy‐Bruhl, D.; The ANRS‐FORMVAC Study Group; et al.
Abstract Despite recommendations for adults at high‐risk of hepatitis B virus (HBV) infection, HBV vaccine uptake remains low in this population. A pre‐post randomized cluster study was conducted to evaluate the impact of on‐site free HBV vaccine availability and/or healthcare worker training on HBV vaccination acceptability in high‐risk adults consulting in 12 free and anonymous HIV and hepatitis B/C testing centres (FATC). The FATC were randomly allocated into three groups receiving a different intervention: training on HBV epidemiology, risk factors and vaccination (Group A), free vaccination in the FATC (Group B), both interventions (Group C). The main outcomes were the increase in HBV vaccination acceptability (receipt of at least one dose of vaccine) and vaccine coverage (receipt of at least two doses of vaccine) after intervention. Respectively, 872 and 809 HBV‐seronegative adults at high‐risk for HBV infection were included in the pre‐ and post‐intervention assessments. HBV vaccination acceptability increased from 14.0% to 75.6% (p <0.001) in Group B and from 17.1% to 85.8% (p <0.001) in Group C and HBV vaccine coverage increased from 9.4% to 48.8% (p <0.001) in Group B and from 11.2% to 41.0% (p <0.001) in Group C. The association of training and free on‐site vaccine availability was more effective than free on‐site vaccine availability alone to increase vaccination acceptability (ratio 1.14; from 1.02 to 1.26; p 0.017). No effect of training alone was observed. These results support the policy of making HBV vaccine available in health structures attended by high‐risk individuals. Updating healthcare workers' knowledge on HBV virus and its prevention brings an additional benefit to vaccination acceptability.